IMPLEMENTATION OF ARTICLES OF HARMONY BETWEEN RELIGIOUS PEOPLE AT M AHABBAH INSTITUTE FOR PEACE AND GOODNESS - Muhammad Arief Syam Syam (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to discuss the implementation of the verses of inter-religious harmony at the Mahabbah Institute for Peace and Goodness. One of the organizations that have made these efforts is the Mahabbah Institute for Peace and Goodnes, which is abbreviated as MIPG. This organization has a vision and mission to maintain religious harmony. Among the efforts that have been made are conducting regular studies involving all elements of religion, including Islam, so that understanding and harmony occur. The results of the research show that the implementation of the verses of harmony at the Mahabbah Institute for Peace and Goodness is divided into two concepts, namely: a) passive tolerance in the form of accepting the existence of different beliefs and not disturbing followers of other religions; b) active tolerance in the form of routine interfaith discussions, reminding each other of religious teachings and maintaining friendship.